2017
DOI: 10.1159/000485342
|View full text |Cite
|
Sign up to set email alerts
|

MiR-148b, MiR-152/ALCAM Axis Regulates the Proliferation and Invasion of Pituitary Adenomas Cells

Abstract: Background/Aims: Aberrant expression of miRNA has been found in many tumor tissues to regulate the tumorigenesis by binding to the 3`- untranslated region (3`-UTR) of the target genes. The aim of this study is to investigate the role of miR-148b, miR-152/ALCAM axis in human pituitary adenomas (PAs). Methods: First, we detected the expression level of miR-148b-3p and miR-152 in human PAs samples by using qRT-PCR. Then we studied the role of miR-148b-3p, miR-152 on human PAs cell proliferation, invasion and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Thus, they control the pathogenesis of the majority of diseases and multiple types of human cancer [2]. miRs regulate all hallmarks of cancer, including the proliferation and invasiveness [3][4][5]. According to the predominant function of given miR in a cancer cell, we can distinguish oncomiRs and tumor suppressor miRs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they control the pathogenesis of the majority of diseases and multiple types of human cancer [2]. miRs regulate all hallmarks of cancer, including the proliferation and invasiveness [3][4][5]. According to the predominant function of given miR in a cancer cell, we can distinguish oncomiRs and tumor suppressor miRs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging data have demonstrated that miRNAs may act as oncogenes or tumor suppressors depending on the functions of their target genes [13]. Previous studies demonstrated that miRNAs play critical roles in pituitary tumorigenesis [14][15][16]. Deep sequencing is a technique that determines the precise order of nucleotides in a strand of DNA/ RNA.…”
mentioning
confidence: 99%
“…He et al . revealed that miR‐152/ALCAM axis modulated pituitary adenomas cells proliferation and invasion . More importantly, in lung adenocarcinama, ALCAM acted as the target of miR‐483 in regulating invasion and metastasis .…”
Section: Discussionmentioning
confidence: 97%
“… He et al . showed that inhibition expression of ALCAM repressed proliferation and invasion of pituitary adenomas cells . Moreover, Ishiguro and his colleagues revealed that knockdown of ALCAM suppressed NSCLC cell migration and invasion and that it was associated with the prognosis of NSCLC patients .…”
Section: Introductionmentioning
confidence: 98%